2009
DOI: 10.2527/jas.2008-1761
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of fatty acids involved in ruminal biohydrogenation in sheep fed concentrate or herbage with or without tannins1

Abstract: A 2 x 2 factorial experiment was carried out to evaluate the effect of herbage or concentrate feeding and dietary tannin supplementation on fatty acid metabolism and composition in sheep ruminal fluid, plasma, and intramuscular fat. Twenty-eight male lambs were divided into 2 equal groups at 45 d of age and kept in individual pens. One group was given exclusively fresh herbage (vetch), and the other group was fed a concentrate-based diet. Within each treatment, one-half of the lambs received supplementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
149
2
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(179 citation statements)
references
References 42 publications
11
149
2
8
Order By: Relevance
“…In fact, previous studies reported that some kinds of plant polyphenols might influence rumen microbe metabolism, affecting the biohydrogenation process of the dietary unsaturated fatty acids (Vasta et al, 2009;Buccioni et al, 2011;JerĂłnimo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies reported that some kinds of plant polyphenols might influence rumen microbe metabolism, affecting the biohydrogenation process of the dietary unsaturated fatty acids (Vasta et al, 2009;Buccioni et al, 2011;JerĂłnimo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This pattern could be because of an additive effect of polyphenols and olive oil contained in the cake. Previous in vitro and in vivo studies, in fact, demonstrated a significant effect of dietary polyphenols on the rumen bacterial community, which resulted in a decrease of BCFA content in both rumen liquor and intramuscular fat (Vasta et al, 2009;Buccioni et al, 2011).…”
mentioning
confidence: 99%
“…Hence, when the present study was planned, two different sources of tannins were selected: chestnut as a source of HT and quebracho as a source of CT. These sources were chosen because widely used in the Mediterranean area as additive in small ruminant diets (Vasta et al, 2009). The percentages and the type of tannins used in this trial did not alter the pH value of rumen liquor, buffered with McDougall solution (McDougall, 1948).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of tannin effects may vary according to differences in -E-mail: arianna.buccioni@unifi.it the structure and molecular weights of both tannins and dietary proteins (Min et al, 2003). Vasta et al (2008Vasta et al ( , 2009Vasta et al ( , 2010 suggested that ruminal biohydrogenation (BH) is affected by CT and that tannins could be a potential means to increase rumenic (RA; C18:2 cis9, trans11) and vaccenic acid (VA; C18:1 trans11) content in food of animal origin. Studies in animal models and in vitro demonstrate that RA has potential anticarcinogenic properties (Benjamin and Spener, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, iso-BCFA are synthesized by cellulolytic strains (the microorganisms mainly involved in ruminal BH; Kepler and Tove, 1967), consequently being considered valuable predictors of ruminal bacterial activity. Tanniferous compounds were reported to reduce considerably the concentration of iso-BCFA in the rumen (Vasta et al, 2009a(Vasta et al, , 2009b(Vasta et al, , 2010.…”
Section: " "mentioning
confidence: 99%